Upaya Penanganan Tinea Capitis Dengan Pendekatan Kedokteran Keluarga Di Puskesmas Simpang Keuramat Kabupaten Aceh Utara - Ulfa Zahara; Noviana Zara; Anita Aris (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
The patient, MA, a 2-year-4-month-old boy, was brought by his mother to Simpang Keuramat Primary Health Center with complaints of itchy scalp for the past 4 months. On the itchy area, white scales were observed. Initially, it was only itching, but two weeks later, the parents noticed white patches on the scalp that became thicker and more scaly. The itching was intermittent and worsened with sweating. At first, only a few hairs were broken, but over time it progressed into a round area of hair loss with well-defined borders. The patient bathes twice daily and shampoos every other day. Towels, pillows, and combs used by the patient were not shared with other family members. According to the patient's parents, the child often plays with stray cats around the house. Primary data were obtained through allo-anamnesis, physical examination, home visits, completion of the family folder, and patient records. Assessment was conducted based on the initial holistic diagnosis, process, and outcome of the visits, both quantitatively and qualitatively. Interventions included educating the patient about the causes of tinea capitis, emphasizing the importance of skin hygiene, and explaining that the disease is highly contagious. Therefore, patients were advised to avoid sharing clothing and towels with family members as a preventive measure against transmission.